(untitled) (Bangladesh Journal of Microbiology, 2019)
Street food contamination is common and has a potential health hazards throughout the world. These categories of foods are very popular among the students of Academic Institutions (Universities) of Dhaka city, Bangladesh for their appealing look and reasonable cost. This study was conducted to determine the presence of E. coli, Shigella sp. and Vibrio sp. in the street foods. Two hundred and forty-two food samples were collected from 20 University premises of Dhaka city. Biochemical tests were performed on suspected colonies for the identification of the relevant bacteria obtained from the samples. E. coli, Vibrio sp., and Shigella sp. were identified in 18% samples, where E. coli was found in 12%, Vibrio sp. was identified in 5%, and Shigella sp. in <1.0% food sample studied. The samples from which E. coli and food borne pathogens were obtained were considered unsatisfactory for human consumption.Presence of enteric bacteria in street foods indicates that the students of different Universities in Dhaka city might be at high risk of food borne disease Bangladesh J Microbiol, Volume 36 Number 1 June 2019, pp 45-47